E-Commerce : Definisi, Perkembangan Dan Hukum Dalam Pandangan Agama Islam - Diki Tri Bagus Dermawan; Dety Mulyanti (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2023)
Introduction: The internet provides various conveniences, including in buying and selling transactions or so-called e-commerce. E-commerce provides many benefits, and there were 2,361,423 e-commerce businesses in Indonesia in 2020. E-commerce is a legitimate buying and selling transaction if it does not deviate from the principles of Islamic sharia law. Purpose: To understand the meaning of e-commerce, its development, and the Islamic law perspective on it. Method: The method used is literature study from relevant journals, books, and fatwas. Results and Conclusion: E-commerce is a buying and selling transaction process carried out through the internet. E-commerce has several advantages compared to traditional commerce, such as the buying and selling process can be done anywhere and anytime. E-commerce in Indonesia has developed since 1999 until now, and it has always been accompanied by improvements. The largest e-commerce service providers in Indonesia are Lazada, Tokopedia, Shopee, Elevania, Bukalapak, Blibli, and Matahari Mal.com. E-commerce has been declared legitimate by MUI, NU, and ulama.